PLATELET-RICH PLASMA GROWTH FACTORS IN RECONSTRUCTIVE IMPLANTIOLOGY OF MUSCULOSKELETAL DEGENERATIVE-DYSTROPHIC DISEASES - Панов, Алексей Александрович; Ланшаков, Виталий Алексеевич (Medicine in Kuzbass, 2018)
The article presents an analysis of the literature on the treatment of tendon injuries in the aspects of bioimplantology, regenerative medicine, reconstructive surgery and the choice of the optimal combination of plastic and biological materials for tendon revitalization in the course of reconstructive treatment.Conclusions. Despite significant advances in regenerative surgery and bioimplantology, there are a number of unresolved issues in the reconstruction of the tendon structure, the selection of the optimal scaffold.
Keywords: degenerative-dystrophic disease; scaffold; platelet-rich autoplasm; growth factors